A simple and rapid HPLC‐UV method for the determination of retigabine in human plasma. (24th January 2018) - Franco, Valentina; Baruffi, Katia; Gatti, Giuliana; Marchiselli, Roberto; Fattore, Cinzia; Canevini, Maria Paola; Crema, Francesca; Perucca, Emilio
Abstract: A simple and rapid high‐performance liquid chromatographic method with ultraviolet detection was developed for the quantitative determination of retigabine, known also as ezogabine, in human plasma. The assay uses a simple solid‐phase extraction for sample preparation and direct injection of the extract into the chromatograph. Flupirtine is used as an internal standard. Chromatographic separation is achieved on a C18 Chromolith column (Chromolith Performance, 100 × 4.6 mm i.d.), using as mobile phase water/acetonitrile/methanol (72:18:10 v/v/v) mixed with 0.1% of 85% phosphoric acid. Isocratic elution is conducted at a flow rate of 1.5 mL min −1 . The total duration of a chromatographic run is 7 min. Calibration curves are linear over the 25–2000 ng mL −1 concentration range, with a limit of quantitation of 25 ng mL −1 . Other performance characteristics include high precision (intra‐ and inter‐day coefficients of variation ≤12.6%) and high accuracy (99.7%–108.7%). The method is suitable for the investigation of concentration–response relationships in patients receiving therapeutic doses of retigabine.